Constraints on the unified model of dark matter and dark energy - 吕剑波 吴亚波 徐立昕 王钰婷 (Chinese physics B, 2011)
Using recently observed data： the Constitution dataset of type supernovae Ia （SNIa）, the observational Hubble data （OHD）, the measurement results of baryon acoustic oscillation （BAO） from the Sloan Digital Sky Survey （SDSS） and the Two Degree Field Galaxy Redshift Survey （2dFGRS）, and the current cosmic microwave background （CMB） data from the five-year Wilkinson Microwave Anisotropy Probe （WMAP）, we apply the Markov Chain Monte Carlo method to investigate the observational constraints on the generalized Chaplygin gas （GCG） model as the unification of dark matter and dark energy. For this unified model, the constraints on GCG mixture are discussed by considering the different expressions of current matter density or considering constraints as being independent of the matter quantity Ωm.